DESIGNING THE SYSTEM OF TARGET INDICATORS AND FIGURES OF BUDGET EXPENDITURE EFFICIENCY AS AN ELEMENT OF BUDGET POLICY - Alena S. Chuvakova (Вестник Российского экономического университета имени Г. В. Плеханова)
Budget policy is a multisided notion. Functioning of bodies of state power and realization of tasks facing society and state depend on the availability of funds and tax policy, identifying a share of profit in the country GDP and priorities of budget expenditure. One element of budget policy is budget expenditure performance, which stipulates the necessity to control the efficiency of budget expenses on the part of society. To improve the efficiency of using national resources and to manage by results we should design a system of target indicators and figures to control the efficiency of budget expenditure. The article discusses aspects of managing risks of using national resources as a line of raising the efficiency of budget expenditure. The author substantiates the proposal to raise the quality of state finance control as a method of enhancing the efficiency of budget expenses.